2019
DOI: 10.1038/s41598-019-45120-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma channel formation in NIR laser-irradiated carrier gas from an aerosol nanoparticle injector

Abstract: Aerosol nanoparticle injectors are fundamentally important for experiments where container-free sample handling is needed to study isolated nanoparticles. The injector consists of a nebuliser, a differential pumping unit, and an aerodynamic lens to create and deliver a focused particle beam to the interaction point inside a vacuum chamber. The tightest focus of the particle beam is close to the injector tip. The density of the focusing carrier gas is high at this point. We show here how this gas interacts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The injector, either with GDVN or ES, can be installed on the top DN250CF port of the MAC chamber on an xyz manipulator. When the injector is in operation, the vacuum level in MAC chamber rises typically to 10 −6 − 10 −5 mbar, still allowing ion or electron spectroscopy [70] (Sect. 4.1, Fig.…”
Section: Aerosol Nanoparticle Injectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The injector, either with GDVN or ES, can be installed on the top DN250CF port of the MAC chamber on an xyz manipulator. When the injector is in operation, the vacuum level in MAC chamber rises typically to 10 −6 − 10 −5 mbar, still allowing ion or electron spectroscopy [70] (Sect. 4.1, Fig.…”
Section: Aerosol Nanoparticle Injectorsmentioning
confidence: 99%
“…In the first commissioning experiments, the gas background from the nanoparticle injector has been thoroughly characterized by the determination of energies of ions created in the interaction with a strong NIR laser field. It has been shown that a plasma channel can be created in the interaction volume and the measured ion energies can be used to estimate the gas density [70].…”
Section: Charged Particle Spectrometers and Photon Detectors 41 Electron And Ion Time-of-flight Spectrometermentioning
confidence: 99%
“…The injector, either with GDVN or ES, can be installed on the top DN250CF port of the MAC chamber on an xyz manipulator. When the injector is in operation, the vacuum level in MAC chamber rises typically to 10 −6 − 10 −5 mbar, still allowing ion or electron spectroscopy [70] (section IV A, Fig. 10(b)).…”
Section: Aerosol Nanoparticle Injectorsmentioning
confidence: 99%
“…al. [7]. Mesoscopic particles dispersed as an effusive jet in a vacuum have been shown to generate hard X-rays with energies up to 100 keV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the collimated beam of nanoparticles by ALS has been studied for ion generation, time-of-flight studies [7] and single particle diffractive imaging [9], their application in high-energy electron generation using laser-plasma interaction remains unexplored. With the growing interest in microtargets for relativistic and nearrelativistic electron production [5,6,20,21], the use of an ALS provides a platform for studying and understanding the physics of laser-plasma interactions in mass-isolated structured targets.…”
Section: Introductionmentioning
confidence: 99%